The role of perceived feasibility and perceived desirability on entrepreneurial behaviour through goal and implementation intentions of students in Southeast Vietnam - Khuyen, Nguyen Tan; Thanh, Le Cao; Tan, Ha Kien; Ghi, Tran Nha (Nurture, 2023)
Purpose: This study examines the relationship between perceived intention (perceived feasibility and perceived desirability), goal and implementation intentions and entrepreneurial behavior of final-year students in Ho Chi Minh City, Binh Duong Province, Dong Nai Province and Ba Ria Vung Tau Province. Vietnamese schools and the government both provide support to students who desire to set up a business. Design/Methodology/Approach: The relationship between perceived intention (perceived feasibility and perceived desirability), goal, implementation intentions and entrepreneurial behavior was determined by the 368 students who have been starting the business using the AMOS-SEM estimation method. Findings: The result shows that perceived feasibility and perceived desirability have positively influenced goal and implementation intentions and goal and implementation intentions have positively impacted entrepreneurial behaviour. Conclusion: In this study, entrepreneurial behaviour is directly explained by two factors, namely goal and implementation intention. It is also indirectly defined by perceived feasibility and desirability. Practical Implications: The study’s findings have implications for both university and student policies. Entrepreneurial ideas and implementation intentions have an impact on behavior. Limitations: Convenient sampling in this study could potentially impact the accuracy of the outcomes in terms of representation. Contribution to Literature: This study extends the Event Entrepreneur model (EEM) by adding the implementation intention factor into the model.